Genome sequence of Streptococcus agalactiae strain 09mas018883, isolated from a Swedish cow - Zubair, S.; Villiers, Etienne P. de; Fuxelius, H.H.; Andersson, G.; Johansson, K.E.; Bishop, Richard P.; Bongcam-Rudloff, E. (American Society for Microbiology, 2013)
We announce the complete genome sequence of Streptococcus agalactiae strain 09mas018883, isolated from the milk of a cow with clinical mastitis. The availability of this genome may allow identification of candidate genes, leading to discovery of antigens that might form the basis for development of a vaccine as an alternative means of mastitis control.